The Auditor-Firm Conflict of Interests: Its Implications for Independence. - Goldman, Arieh; Barlev, Benzion (The Accounting Review, 1974)
This article focuses on how the autonomy of auditors in the performance of their professional duties has always been considered a cornerstone of the profession. In this respect, auditing is similar to other professions. There is a feeling, however, that the autonomy of auditors is being undermined. This is shown by the many rulings of professional bodies on this issue, the elaborate rules of conduct designed to strengthen autonomy, the many articles in professional journals devoted to this subject, and even by the coining of a special term to denote this problem: "independence." The purpose of this article is to explain why the independence issue has become so central in auditing, to indicate possible methods of dealing with this problem, and to suggest a framework for their evaluation. Auditing is defined as an examination intended to serve as a basis for an expression of opinion regarding the fairness, consistency, and conformity with accepted accounting principles of statements prepared by a corporation or other entity for submission to the public or to other interested parties.